Exploring the challenges faced by social workers in managing the cases of unaccompanied minors in the child and youth care centres in Polokwane Municipality - Nkwana, Matlou Julia (My University, 2021)
Since transition from the system of apartheid to democratic rule, South Africa became the destination for many migrants and refugees from across the African continent. Many children are travelling alone or become separated from their care givers or parents once they reach the country. The migration of residents of other African countries, particularly Zimbabwe, into the Limpopo province has resulted in the increase in the number of unaccompanied minors within the province, in Polokwane and the child protection system, and it requires collaborative intervention. The child protection system, particularly in the Child and Youth Care Centres, has unaccompanied minors who remain in the system for more than the stipulated time in relation to the Children’s Act 38 of 2005. The aim of the study was to explore the challenges faced by social workers in managing the cases of unaccompanied minors in Child and Youth Care Centers in Polokwane. This study employed a qualitative case study research design and one-on-one interview as a primary data collection method. The qualitative data was analysed using a thematic approach. The findings of this study indicate that most of unaccompanied minors were in dire situation and lack proper documentation. The findings also revealed that there were a number of critical child protection challenges that existed in the management of the cases of unaccompanied minors by government officials. The study further highlighted that social workers were not adequately capacitated and there was lack of intersectoral collaboration and insufficient resources to deal with the multiple issues that affect unaccompanied minors in Polokwane. It is therefore recommended that the social worker should also be capacitated regarding different items of legislation that deal with unaccompanied and foreign children in order to ensure proper implementation of the Acts. Department of Social Development must also popularise and provide training to social workers and all relevant stakeholders on the guidelines on separated and unaccompanied minors living outside their country of origin. DSD should make an amendment of the Children’s Act to include unaccompanied minors and also ensure that all stakeholders are trained. The researcher also recommends coordination of service among government departments in order to ensure an effective and integrated child protection system
Thesis (M. Dev. (Development in Planning and Management)) -- University of Limpopo, 2021
Keywords: Social workers; Child and youth care centres; Unaccompanied Minors; Humanitarian assistance -- South Africa; Unaccompanied children -- Government policy -- South Africa; Unaccompanied refugee children